PEMISAHAN SENYAWA FENOL DARI LIMBAH CAIR INDUSTRI PULP (Black Liquor) DENGAN CARA FRAKSINASI - DISTILASI - R Sudradjat; Aldi P Johor Ning (Jurnal Penelitian Hasil Hutan, 1993)
The aim of the experiment is to study phenol recovery from waste liquor of pulp and paper processing industry.The method used for selecting distillation procedure were simple distillation, distillation design A, B, C, D, E, F and F-m as mentioned in the procedure. The pH of substrate used were 14, 12, 10, and 9 while for absorbents were 1, 3, 5 and 7. Distillation time used varied from 3.15 ; 5.15 ; and 7.15.The result shows that the highest phenol recovery was obtained from the design F-m yielding 75. 3 % phenol recovery during 5 hours 15 minutes distillation time, using substrate having pH of 14 and absorbent pH of 3. Applying such method on sulphite black liqour, gave 56.3 % phenol recovery.